2021
DOI: 10.1002/jclp.23161
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive vulnerabilities to anxiety symptoms among Chinese adolescents: A 3‐year longitudinal study

Abstract: Objective: This study established cognitive vulnerability of anxiety symptoms among high school students.Method: A total of 72 grade 9-11 students completed measures on levels of anxiety sensitivity (AS), selective attentional processing, and anxiety symptoms annually between 2016 and 2018.Results: Latent class growth analysis (unconditional model) showed a four-class model: High (stable) (6.94%), low (stable) (11.11%), medium (decreasing) (61.11%), and medium (increasing) (20.83%). The conditioned model contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Therefore, consistent with the validity of the full scale byNoguchi et al (2006a), the convergent and discriminant validity of the 7-item CAPNIS was good.Importantly, negative attentional bias and positive attentional bias measured by the two subscales in the 7-item CAPNIS were associated concurrently with fear of COVID-19, anxiety, and depression symptoms. Consistent with previous studies(Ho et al, 2018;Ho et al, 2021), high negative attentional bias was related to high emotional symptoms; while high positive attentional bias was associated with low emotional symptoms in Chinese adolescents. This evidence further corroborated that Attention to Negative Information was related to negative affectivity as demonstrated byNoguchi et al (2006a).The predictive validity of ANI for fear of COVID-19 was good, even after controlling for fear of COVID-19, anxiety, and depression at T1.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, consistent with the validity of the full scale byNoguchi et al (2006a), the convergent and discriminant validity of the 7-item CAPNIS was good.Importantly, negative attentional bias and positive attentional bias measured by the two subscales in the 7-item CAPNIS were associated concurrently with fear of COVID-19, anxiety, and depression symptoms. Consistent with previous studies(Ho et al, 2018;Ho et al, 2021), high negative attentional bias was related to high emotional symptoms; while high positive attentional bias was associated with low emotional symptoms in Chinese adolescents. This evidence further corroborated that Attention to Negative Information was related to negative affectivity as demonstrated byNoguchi et al (2006a).The predictive validity of ANI for fear of COVID-19 was good, even after controlling for fear of COVID-19, anxiety, and depression at T1.…”
supporting
confidence: 90%
“…The Attention to Negative Information subscale demonstrated internal consistencies (α = . Chinese women (ANI: 0.84; API: 0.87) (Ho et al, 2021). Therefore, the 3-item API scale had lower internal consistency than the full version of APNIS.…”
Section: Reliabilitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…A longitudinal study showed that low positive attentional bias measured by spatial orienting tasks might cause increased depression and anxiety symptoms for adolescents of 16 years (Vrijen, Hartman, & Oldehinkel, 2019). For negative attentional bias, a longitudinal study revealed that high negative attentional bias measured by the selfreport inventory predicted the developmental trajectories of high anxiety in children of 9 to 11 years over three years (Ho, Zhang, Lai, & Dai, 2021). Interventions that reduce negative attentional bias, including attentional bias modi cation, have shown e cacy in relieving anxiety and depression symptoms in children and adolescents (Krejtz, Holas, Rusanowska, & Nezlek, 2018;Kress & Aue, 2019;McDermott & Dozois, 2015).…”
Section: Attentional Bias and Internalizing Symptomsmentioning
confidence: 99%
“…Therefore, other methods to assess attentional bias might be needed to increase our understanding of attentional bias. For negative attentional bias, a longitudinal study revealed that high negative attentional bias measured by the self-report inventory predicted the developmental trajectories of high anxiety symptoms in 72 Chinese children from grade 9 to 11 in high schools over three years [ 11 ]. The self-report inventory of attentional bias such as the Attention to Positive and Negative Information Scale had good reliabilities and validities [ 23 ].…”
Section: Introductionmentioning
confidence: 99%